2019
DOI: 10.1186/s12967-019-1931-2
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic value of TIM-1 expression in human non-small-cell lung cancer

Abstract: Background T-cell immunoglobulin and mucin domain 1 (TIM-1) is an important co-stimulatory molecule which serves as a surface marker for T cell activation, especially for Th2 cells. Recently, many studies have also shown that TIM-1 can be abnormally expressed in human cancers and may have a potential role in promoting cancer progression. Methods The immunohistochemistry was used to examine the TIM-1 expression in human non-small-cell lung carcinoma (NSCLC) tissues. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
29
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(30 citation statements)
references
References 33 publications
1
29
0
Order By: Relevance
“…Moreover, the overall survival rate of non-small-cell lung cancer patients with high expression of TIM-1 is significantly lower than that of patients with low expression of TIM-1. In cell experiments, it was also found that inhibition of TIM-1 expression could inhibit the migration and invasion ability of A549 and SK-MES-1 cells in vitro, respectively (43). All these suggest that TIM-1 plays an important role in the invasion and metastasis of cancers.…”
Section: Discussionmentioning
confidence: 86%
“…Moreover, the overall survival rate of non-small-cell lung cancer patients with high expression of TIM-1 is significantly lower than that of patients with low expression of TIM-1. In cell experiments, it was also found that inhibition of TIM-1 expression could inhibit the migration and invasion ability of A549 and SK-MES-1 cells in vitro, respectively (43). All these suggest that TIM-1 plays an important role in the invasion and metastasis of cancers.…”
Section: Discussionmentioning
confidence: 86%
“…11 Studies have identified that Tim-1 is expressed in many human tumor tissues. 19,20,29,30 Tim-1 is presented in cancer cells, in CD68-positive macrophages and CK-18-positive epithelial cells 29 in human Langerhans cell sarcoma. Liu et al 30 have revealed Tim-1 levels in human gastric cancer tissues are upregulated, indicating the prognostic application of Tim-1 in gastric cancer patients.…”
Section: Discussionmentioning
confidence: 99%
“…Zheng et al found down-regulation of Tim-1 caused by RNA interference could block cellular events of NSCLC cells. 20 Accordingly, Tim-1 is an underlying therapeutic target for human cancers.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations